Morphology and molecular characterization of Pseudo-nitzschia (Bacillariophyceae) from Malaysian Borneo, including the new species Pseudo-nitzschia circumpora sp. Nov - Hong-Chang, Lim; Chui-Pin , Leaw; Nyun-Pau Su, Suriyanti; Sing-Tung, Teng; Usup, Gires; Mohammad Noor, Normawaty; Lundholm, Nina; Kotaki, Yuichi; Po-Teen , Lim (Phycological Society of America, 2012)
Field sampling was undertaken to investigate the occurrence of Pseudo-nitzschia Peragallo species in eight locations along the coast of Malaysian Borneo. A total of 108 strains of Pseudo-nitzschia species were isolated, and their morphology examined with SEM and TEM. Additionally, molecular data from nuclearencoded partial LSU rDNA, and ITS regions, were characterized. A total of five species were confidently identified based on a combination of distinct morphological characteristics and supporting molecular evidence: P. brasiliana Lundholm, Hasle & Fryxell, P. cuspidata (Hasle) Hasle, P. dolorosa Lundholm & Moestrup, P. micropora Priisholm, Moestrup & Lundholm, and P. pungens (Grunow) Hasle var. pungens. However, one morphotype from Sarawak, while somewhat similar to P. caciantha, showed significant morphological distinction from this and any other of the currently described species. Most notably this morphotype possessed a characteristic pore arrangement in the poroids, with the fine pores in each perforation sector arranged in circles. Pairwise sequence comparison of the LSU rDNA between this unidentified morphotype and P. caciantha Lundholm, Moestrup & Hasle, revealed 2.7% genetic divergence. Phylogenetic analyses strongly supported the monophyly of the morphotype. Based upon these supporting data it is here described as a new species, Pseudo-nitzschia circumpora sp. nov. A key to the six species of Pseudo-nitzschia from Malaysian Borneo is presented. Molecular signatures for all species were established based on structural comparisons of ITS2 rRNA transcripts.